EFL Students’ Difficulties in Writing Narrative Text - Nova Falihah; Eri Rahmawati; Akhmad Baihaqi (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2022)
The purposes of this study are to identify the difficulties faced by students in writing narrative texts and to determine the factors that caused students’ difficulties in writing narrative texts. This research used qualitative research with a case study method. Data were collected from observations, questionnaires, and documentation. The participants in this study were tenth-grade students of one public high school in Serang, Banten Province. From the results of the study, there are four difficulties most agreed upon by students in writing narrative texts, namely students’ difficulties in (1) writing correct sentences, (2) using appropriate tenses, (3) using appropriate vocabulary, and (4) developing the ideas. Meanwhile, the factors causing students' difficulties in writing narrative texts that they are mostly agree with the limited vocabulary and they cannot write structured sentences in English. Based on the results of the study, it can be concluded that the difficulties faced by students in writing narrative texts are difficulties in grammar and vocabulary. Then, the factors that cause students difficulties in writing narrative texts are limited vocabulary and inability to understand the grammar well.